Hormonal Contraception and Bone Metabolism: Emerging Evidence from a Systematic Review and Meta-Analysis of Studies on Post-Pubertal and Reproductive-Age Women - Alice Tassi; Ambrogio P Londero; Anjeza Xholli; Giulia Lanzolla; Serena Bertozzi; Luca Savelli; Federico Prefumo; Angelo Cagnacci (Pharmaceuticals)
Background/Objectives: This study aims to assess the effects of combined hormonal contraceptives (CHCs) on bone metabolism markers. It primarily measures osteocalcin and additionally examines other bone health markers, seeking to determine their responses to estrogen–progestogen treatments. Methods: This study involved a comprehensive evaluation of the pertinent literature and a meta-analysis explicitly conducted on data describing women of reproductive age. The analysis encompassed accessible papers ranging to December 2024 (i.e., those listed in PubMed/Medline, Embase, Scopus, the Cochrane Database, International Clinical Trials Registry, and ClinicalTrials.gov). We examined published randomized controlled trials (RCTs) and prospective studies. The quality of the studies was assessed using the Cochrane tool for RCTs and the Newcastle–Ottawa Scale for prospective studies. The selected indicators for primary and secondary outcomes were ascertained by standardized mean change (SMC), displaying the difference between conditions before and after treatment. Trends were evaluated using meta-regressions. Results: Ultimately, 34 articles out of 1924 identified items met the inclusion criteria, covering 33 unique studies. In EE/E4 combinations, osteocalcin dropped significantly (SMC −0.54 (CI.95 −0.64/−0.43) and −0.43 (CI.95 −0.76/−0.10)). Similar effects were observed for other bone-formation and reabsorption markers, with less significant reductions observed in E2-containing CHC (e.g., alkaline phosphatase (bone) EE combinations, SMC −0.39 (CI.95 −0.67/−0.11); P1NP E2 combination, 0.12 (CI.95 −0.10/0.33); and EE combinations, −0.55 (CI.95 −0.83/−0.26)). The reduction patterns also exhibited differences according to the women’s age (e.g., osteocalcin in EE combinations ≤21, SMC −0.63 (CI.95 −0.77/−0.49) and >21, SMC −0.42 (CI.95 −0.61/−0.24); alkaline phosphatase (bone) EE combinations ≤21, SMC −0.55 (CI.95 −0.86/−0.24) and >21, SMC −0.06 (CI.95 −0.47/0.35)). This analysis found that CHC maintains or reduces bone turnover in childbearing women, with effects varying by age and hormone combination. Moreover, bone-formation and reabsorption markers correlated positively to pro-androgenic progestins (p < 0.05). Thus, estrogen–progestogen combinations reduce bone turnover less when weak estrogens and a pro-androgenic or neutral progestin are present. Conclusions: This study found that CHCs reduce bone turnover, with natural estrogens and androgenic progestins appearing to be more beneficial than EE and anti-androgenic types. These findings would potentially influence decisions relevant to CHC prescriptions during a woman’s reproductive phases, emphasizing the need for additional research to tailor CHC usage to bone health.